POLA ASUH IBU TENAGA MEDIS DALAM MEMBANGUN GAYA HIDUP SEHAT DAN POLA KONSUMSI ANAK : STUDI KUALITATIF - Rosatias Tisa Putri; Mutimmatul Faidah (LPPM Universitas Negeri Surabaya, 2026)
This study aims to analyze the parenting practices of mothers working as healthcare professionals in promoting healthy lifestyles and family consumption patterns in the modern era. A descriptive qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and documentation involving one family in which the mother is a healthcare worker. The study focuses on the mother’s role as a health agent in daily family life, particularly in regulating dietary habits, physical activity, and stress management. The findings indicate that the parenting style applied is adaptive and participatory, characterized by role modeling of healthy behaviors, open communication, and flexible rule-setting. The mother acts as a facilitator who encourages active involvement of family members in maintaining health, despite time constraints resulting from her dual roles. The implementation of a healthy lifestyle is reflected in regular light physical activities, regulated eating and sleeping patterns, and family-based stress management practices. These findings suggest that mothers who are healthcare professionals play a significant role in fostering physical and mental health balance within the family.